(untitled) (The Review of Diabetic Studies, 2025)
Acute myocardial infarction (AMI) remains a leading cause of global morbidity and mortality, where rapid prehospital assessment and early intervention are critical to improving patient outcomes. Paramedics play an essential frontline role in the early phases of AMI care by providing timely recognition, rapid triage, and evidence-based treatments before hospital arrival. This review synthesizes contemporary evidence on the impact of prehospital paramedic interventions on survival rates, treatment timelines, and clinical outcomes among patients experiencing AMI. Findings demonstrate that advanced paramedic competencies—such as early 12-lead electrocardiogram (ECG) acquisition, prehospital STEMI identification, activation of cardiac catheterization laboratories (CCLs), and administration of antiplatelet therapy—significantly reduce first medical contact-to-balloon time and overall door-to-balloon intervals. Moreover, paramedic-initiated treatments, including aspirin, nitrates, oxygen titration, arrhythmia management, and prehospital thrombolysis in selected settings, contribute to improved survival and decreased complication rates. The review also highlights the growing role of telemedicine, digital ECG transmission, and AI-supported decision tools in enhancing diagnostic accuracy and accelerating definitive care. Overall, the evidence strongly supports that paramedic-led prehospital AMI management is a critical determinant of timely reperfusion, reduced mortality, and better functional outcomes.